POTENCY OF BIOCONTROL AGENTS ISOLATED FROM COMPOST AND PEAT SOIL OF TROPICAL PEAT SWAMP FOREST IN KALAMPANGAN ZONE, CENTRAL KALIMANTAN - Yuliar Yuliar; Zaenal Abidin; Wibowo Mangunwardoyo (Indonesian Journal of Forestry Research, 2011)
Rhizoctonia solani is a soil pathogen that causes diseases in wide range of hosts of agricultural, horticultural and flower crops. Biological control is the most promising way for the diseases management and it is environment friendly too. The objective of this study was to isolate and screen the potency of soil bacteria as biological control from various local compost and peat soil of tropical peat swamp forest in Kalampangan Zone, Central Kalimantan. Forty seven isolates from peat soil and compost were screened for biocontrol agent of Rhizoctonia solani . R. Solani Seven out of thirteen peat soil isolates, and six out of thirty three compost isolates showed antagonistic activity against in Potato Dextrose Agar. The cultivation of the antagonistic isolates in Trypticase Soy Broth (TSB) was extracted and analysed by high performance liquid chromatography (HPLC) column. The HPLC analyzes indicated that the antagonistic isolates produce an antifungal iturin A. Macroscopic observation of isolates colonies showed that form of their colonies were amuboid, myceloid, curled, circular, rhizoid, irregular and filamentous. These achievement indicate peat swamp forest not only offer a potential biocontrol agents of damping off but also provide a new source for production of antibiotics.